Medical and biological aspects of synanthropic Collembola - V. I. Pavlichenko; A. В. Prihodko; M. V. Steblyuk (Zaporožskij Medicinskij Žurnal)
Many species of synantropic Collembola living in close association with man. Some species for example Wolowsia buski can invade the hair of the head. Some patient think that Collembola cause dermatitis, but doctors diagnose the «delusional parasitosis».